2020
DOI: 10.1021/acsaem.0c00597
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Lithium Aluminate Nanoflake-Inlaid Sulfur as a Cathode Material for Lithium–Sulfur Batteries with High Areal Capacity

Abstract: Direct Utilization of commercial sulfur as a cathode material is ideal for the bulk production of high-energy-density lithium−sulfur (Li−S) batteries. However, due to large ion-diffusion length, commercial sulfur suffers from low practical capacity. To achieve adequate capacity with long-term cyclability using the commercial sulfur-based cathodes, we introduce ultrathin lithium aluminate (LiAlO 2 ) nanoflakes as polysulfide immobilizers with excellent Li + ion conductivity. The ultrathin LiAlO 2 nanoflake-inla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…[ 68 ] Ghosh et al investigate the electrocatalysis of LiAlO 2 nanoflake on the redox kinetics of Li–S batteries by in situ Raman techniques coupled with the chronoamperometry (Figure 7c). [ 69 ] The battery was discharged to 2.2 V and held at this potential, during which in situ Raman spectra were collected. A new peak assigning to S 4 2− moiety at around 234 cm −1 appears in the Raman spectra, suggesting the enhanced chemical reduction of long‐chain LiPSs to Li 2 S 4 .…”
Section: The Application Of In Situ/operando Raman For Li–s Batteriesmentioning
confidence: 99%
“…[ 68 ] Ghosh et al investigate the electrocatalysis of LiAlO 2 nanoflake on the redox kinetics of Li–S batteries by in situ Raman techniques coupled with the chronoamperometry (Figure 7c). [ 69 ] The battery was discharged to 2.2 V and held at this potential, during which in situ Raman spectra were collected. A new peak assigning to S 4 2− moiety at around 234 cm −1 appears in the Raman spectra, suggesting the enhanced chemical reduction of long‐chain LiPSs to Li 2 S 4 .…”
Section: The Application Of In Situ/operando Raman For Li–s Batteriesmentioning
confidence: 99%
“…Compared with traditional insertion lithium-ion batteries, LSBs are promising energy storage systems for the next generation due to their high theoretical capacity (1675 mAh·g −1 ) and high energy density (2600 Wh·kg −1 ) [ 2 , 3 ]. However, the practical implementation of Li-S continues to face formidable challenges, such as the poor electrical conductivity of sulfur, the series of polysulfide intermediates (Li 2 Sn, 6 ≤ n ≤ 8) that can dissolve in electrolytes, and the intermediate polysulfides that diffuse to form shuttle effects, which cause pronounced capacity fading [ 4 ]. Further, during charging and discharging, the conversion between sulfur and Li 2 S/Li 2 S 2 can damage the electrode structure and lead to a number of problems such as rapid capacity loss [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…[12] It was also shown that using ultrathin Lithium aluminate nanoflakes as a polar additive, having an enormous active surface area to immobilize the lithium polysulfides, leads to extremely stable cycling performance in batteries. [13] Furthermore, one-dimensional forms of strontium-europium-based aluminates are luminescent nanoribbons that can function as both light generators and waveguides, and therefore they are suitable materials for miniaturized photonic circuitry. [14] In addition to experimental studies, stabilization of single layer α-AlO displaying indirect semiconducting behavior was also predicted theoretically.…”
Section: Introductionmentioning
confidence: 99%